Use of 3 Tools to Assess Nutrition Risk in the Intensive Care Unit. (January 2015) - Coltman, Anne; Peterson, Sarah; Roehl, Kelly; Roosevelt, Hannah; Sowa, Diane
Background: Identifying patients at nutrition risk proves difficult in the intensive care unit (ICU) due to the nature of critical illness. No consensus exists on the most appropriate method to identify these patients. Traditional screens and assessments are often limited due to their subjective nature. The purpose of the quality improvement project was to compare proportions of ICU patients deemed at nutrition risk using 3 different tools. Material and Methods : A convenience sample of 294 patients admitted to the ICU was used. Patients were assessed using the institution's routine nutrition screening method, the Subjective Global Assessment (SGA), and the NUTrition Risk in Critically ill (NUTRIC) score. Information was collected on demographics, severity of illness, hospital and ICU length of stay (LOS), and disposition. Descriptive statistics were used to examine counts/proportions of risk categories; means ± SD were used to summarize demographic and clinical variables. Results : A total of 139 patients (47%) were deemed at nutrition risk or malnourished by at least 1 tool. Patients identified were older and had a lower body mass index, more weight loss, more fat and muscle wasting, more fluid accumulation, and lower average handgrips than those not at nutrition risk; they also had longer hospital and ICU LOS, higher rates of requiring further rehabilitation upon discharge, and higher mortality during hospitalization. Conclusion : Traditional screening and assessment tools did not uniformly identify patients as malnourished or at nutrition risk in the ICU and therefore may be inappropriate for use in this population. Inclusion of physical assessment, functional status, and severity of illness may be useful in predicting nutrition risk in the ICU.